Study on the Production of Superior Seed Bunches of Oil Palm (Elaeis guineensis Jacq.) (Case Study: Indonesian Oil Palm Research Institute-PPKS Marihat Unit) - Yabani Yabani; Retna Astuti Kuswardani; Agus Susanto; Saipul Sihotang (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
This research aims to examine the production of superior oil palm seed bunches in the PPKS Marihat Unit.Data and information collection is carried out using direct and indirect methods. Field observations carried out include: Area conditions including: topography, soil conditions, Plant conditions including: plant growth, plant population and fruit condition, Technical culture conditions: fertilization, harvesting of seed bunches. Supporting data collected includes: garden production data, rainfall and fertilization data. The research results are bSeveral factors that cause low production include: a) fertilizer amounts that are far from plant needs, given the time, type; b) plant density which is classified as less than optimal due to ganoderma attacks. The number of bunches is the result of plant physiological processes, mainly determined by the ecophysiological conditions of the plant around 24 months before harvest, where the decrease in production in the number of bunches harvested in 2020 is the result of ecophysiological conditions in the form of fertilization which is not appropriate in 2019-2020.